Wie die Umsetzung einer Schule für Menschen mit Parkinson-Krankheit gelingen kann – Ergebnisse eines Konsensusverfahrens und einer formativen Evaluation - Gerschel, Tanita; Prokop, Scally; Schulze, Lara; Feige, Tim; Zschieschang, Anja; Barbe, Michael Thomas; Bitterlich, Robert; Caffier, Julian; Csoti, Ilona; Eggers, Carsten; Gaßner, Heiko; Gülke, Eileen; et al. (Der Nervenarzt, 2024)
Background: As the most rapidly increasing neurodegenerative disease worldwide, Parkinson’s disease is highly relevant to society. Successful treatment requires active patient participation. Patient education has been successfully implemented for many chronic diseases, such as diabetes and could also provide people with Parkinson’s disease with skills to manage the disease better and to participate in shared decision making. Material and methods: To prepare the implementation of a concept for patient education for people with Parkinson’s disease, a structured consensus study was conducted and a pilot project formatively evaluated. The structured consensus study included experts from all over Germany. It consisted of two online surveys and an online consensus conference. The formative evaluation was conducted as three focus groups. Transcripts were evaluated using content-structuring qualitative content analysis. Results: From the consensus procedure 59 consented statements emerged, mainly regarding the contents of a patient school and a group size of 6–8 persons. Only two statements could not be consented. The formative evaluation detected a tendency towards a positive attitude for a digital training format and a very positive evaluation of the contents. Discussion: Overall, important recommendations for a patient school can be drawn from this study. The following subjects require further investigation: format, inclusion criteria, group composition and inclusion of caregivers.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Chronic disease; Expert panel; Patient participation; Quality management; Self-management education